Health-related quality-of-life improvements during 98 weeks of infliximab therapy in patients with plaque-type psoriasis in real-world practice - Shear, Neil H.; Hartmann, Martin (Quality of life research, 2016)
We evaluated the effect of plaque-type psoriasis on health-related quality of life (HRQoL) of patients who received infliximab (IFX) in real-world clinical settings.
Gesehen am 06.05.2020